A cohort study comparing the severity and outcome of intrauterine adhesiolysis for Asherman syndrome after first- or second-trimester termination of pregnancy. (July 2019) - Zhu, Ru; Gan, Lu; Wang, Sha; Duan, Hua
Abstract: Objective: To compare the clinical characteristics of Asherman syndrome and the outcomes of hysteroscopic adhesiolysis in women after first or second-trimester termination of pregnancy (TOP). Methods: This was a retrospective descriptive analysis of patients with moderate-to-severe intrauterine adhesiolysis (IUAs) after TOP and treated by hysteroscopic adhesiolysis and followed by "second-look" hysteroscopy 3 months later at The Beijing Obstetrics and Gynecology Hospital (China) between January 2013 and March 2016. The American Fertility Society (AFS) scoring system was used to evaluate the intrauterine adhesions. Results: A total of 236 patients with 180 first-trimester TOP and 56 s-trimester TOP patients were included. The severe adhesion and amenorrhea rates during the second-trimester group (69.6% and 39.3%, respectively) were significantly higher than those in the first-trimester group (36.7% and 7.2%, respectively). AFS score reduction in the second-trimester group (6.2 ± 2.8) was significantly lower than in the first-trimester group (6.5 ± 2.5). The pregnancy rates in the second-trimester group (21.4%) were significantly lower than that in the first-trimester group (43.3%). The pregnancy rate of severe intrauterine adhesions in second-trimester TOP (10.3%) was significantly lower than in first-trimester TOP (40.9%). Conclusion: These findings suggested that second trimester TOP was associated with more severe intrauterine adhesion and a worse prognosis after hysteroscopic adhesiolysis in women with Asherman syndrome when compared to first-trimester TOP.